The division of mukim and gampong traditional areas in customary forest management in Aceh Province, Indonesia - Mansur, Teuku Muttaqin; Adli, Muhammad; Sulaiman, Sulaiman; Muazzin, Muazzin; yahya, azhari (Geuthèë Institute, Aceh, 2024)
The article 1 paragraph (2) the regulation No 11 of 2006 concerning the Aceh Government (UUPA), Aceh is a provincial region which is a special legal community unit and is given special authority to regulate and manage its own government affairs and the interests of the Acehnese people. Mukim is a form of government in Aceh which is recognized its existance based on the Regulation No 44 of 1999 concerning the Implementation of the Prefentiality Province of the Aceh Prefential Region and UUPA. The legal provision for customary forest management, the Mukim and Gampong have the right to control customary forests in their area for the benefit of their members or people outside the community. This research aims to identify the division of Mukim and Gampong areas in customary forest management. The research method used is empirical juridical. The data was obtained through the field research by means of observation, direct interviews with respondents, reviewing applicable legal provisions and what has happened in people's lives. The research result shows that Mukim and Gampong have their area boundaries themselves which strengthen the division of Mukim and Gampong positions to provide accuracy regarding the control and management of customary forests in their areas, one of them is fulfilling the customary forest management. The division of Mukim area from the hereditary have been exists alrady, but there is still a discourse where the government does not have the same perception as the Mukim customary forests because they think there is a legal basis but it is still invalid or it has not accurate to state the mukim adat areas.